Creating togetherness in a historically divided maternity care system / Zusammengehörigkeit in einem historisch gespaltenen geburtshilflichen Versorgungssystem herstellen - Molenaar Joyce M.; Lips Sarah R.; Teunissen Pim W.; Vermeulen Gea; Schuitmaker-Warnaar Tjerk Jan (Sciendo, 2020)
Improving collaboration in Dutch maternity care is seen as essential to improve continuity of care and thereby safety, client satisfaction, and health outcomes. This study aims to monitor and evaluate whether the regional Maternity Care Network Northwest Netherlands (MCNNN) and its local multidisciplinary obstetric partnerships contributed to collaboration. This mixed-method study followed the methodology of reflexive monitoring in action. Data were collected from 2014 to 2016 through interviews (n=73), questionnaires (n=430), and reflection sessions (n=4) and analyzed inductively and deductively based on a model for interprofessional and interorganizational collaboration. The findings outline (1) MCNNN-activities, (2) experienced collaboration within obstetric partnerships, and (3) MCNNN as supporting structure. The findings showed improvements on both the relational and organizational level of interprofessional and interorganizational collaboration. The MCNNN's meetings, products, and research projects facilitated knowledge development and dissemination and its obstetric partnerships fostered contact and deliberation among maternity care professionals. However, collaborative challenges were also experienced, including mistrust and difficulties in information sharing, influenced by lacking financial and organizational facilitation. The MCNNN could improve its supporting role in the system innovation toward integration in maternity care by means of a further transformation to a knowledge network that is focused on reflexively overcoming collaborative challenges at all levels in the maternity care system.